PENGARUH HEMOLISIS DALAM SERUM TERHADAP AKTIVITAS ENZIM ASPARTAT AMINOTRANSFERASE DENGAN METODE KINETIK-IFCC - Hilda Dila Wanti; Fitri Fadhilah; Opik Taufiqurrohman (Journal of Indonesian Medical Laboratory and Science, 2020)
The aspartate aminotransferase (AST) enzyme is a mitochondrial enzyme that functions to catalyze the alternating transfer of amino groups from aspartic acid to ?-oxaloacetic acid to form glutamic acid and oxaloacetic acid. AST is present in erythrocytes so that if hemolysis occurs, the erythrocytes rupture will cause an increase in the activity of the AST enzyme that comes out of erythrocytes. This study aims to determine the effect of hemolysis in serum on the examination of AST enzyme activity. This research method is experimental by comparing normal serum with serum hemolysis. The research sample involved 16 students who would be examined for AST enzyme activity. The results showed that the activity of AST enzymes in normal serum had an average of 24.63 IU / L whereas in serum hemolysis there was an average of 39.38 IU / L. The results of the data showed that there was an increase in AST enzyme activity in serum hemolysis compared to normal serum. The data were then analyzed using the T test, and the Sig. 0.001 where p <0.05 proved that AST enzyme activity in normal serum and serum hemolysis was stated to be significantly different.